Identification of genomic changes associated with cisplatin resistance in testicular germ cell tumor cell lines. - Noel, E; Perry, J; Chaplin, T; Mao, X; Cazier, J; Joel, S; Oliver, RT; Young, B; Lu, Y (2008)
Since the introduction of cisplatin into the clinic, the treatment of patients with a variety of solid tumors including testicular germ cell tumors, ovarian and lung cancers, has dramatically improved. One of the main causes for therapeutic failure in these malignancies is the development of drug resistance. Testicular germ cell tumors (TGCTs), the most common malignancy in young men, exhibit extreme sensitivity to cisplatin-based chemotherapy, making them an ideal model for investigating the mechanisms of cisplatin chemo-sensitivity and resistance. TGCT development and pathogenesis have been well studied but little is known about the genetic background in chemo-resistant cases. We investigated genomic differences between three TGCT parental cell lines and their cisplatin resistant derivatives. Using 10K single nucleotide polymorphism (SNP) microarray analysis, we identified two small chromosomal regions with consistent copy number changes across all three pairs of resistant cell lines. These were an 8.7 Mb region at 6q26-27, which displayed consistent copy number gain and a 0.3 Mb deletion involving 4 SNPs at 10p14. Both the chromosomal gain and loss were confirmed by fluorescence in situ hybridization. The significance of these regions should be further investigated as they may contain key genes involved in the development of chemo- resistance to cisplatin-based treatment in TGCTs and other cancers.